Lateralization of facial emotion processing and facial paresis in Vestibular Schwannoma patients - Blom, Stephanie (2021)
This study investigates whether there exist differences in lateralization of facial emotion processing in patients suffering from Vestibular Schwannoma (VS) based on the presence of a facial paresis and their degree of facial functioning as measured by the House Brackmann Grading scale (HBG).